Antioxidant and mercury chelating activity of Psidium guajava var. pomifera L. leaves hydroalcoholic extract. Issue 23 (17th December 2017) - Pinho, Antonio Ivanildo; Oliveira, Cláudia Sirlene; Lovato, Fabricio Luís; Waczuk, Emily Pansera; Piccoli, Bruna Candia; Boligon, Aline Augusti; Leite, Nadghia Figueredo; Coutinho, Henrique Douglas Melo; Posser, Thais; Da Rocha, João Batista Teixeira; Franco, Jeferson Luis
ABSTRACT: Mercury (Hg) is widely distributed in the environment and is known to produce several adverse effects in organisms. The aim of the present study was to examine the in vitro antioxidant activity and Hg chelating ability of the hydroalcoholic extract of Psidium guajava leaves (HEPG). In addition, the potential protective effects of HEPG against Hg(II) were evaluated using a yeast model ( Saccharomyces cerevisiae ). HEPG was found to exert significant antioxidant activity in 2, 2-diphenyl-1-picrylhydrazyl scavenger and inhibition of lipid peroxidation induced by Fe(II) assays in a concentration-dependent manner. The extract also exhibited significant Hg(II) chelating activity. In yeast, Hg(II) induced a significant decrease in cell viability. In contrast, HEPG partially prevented the fall in cell viability induced by Hg(II). In conclusion, HEPG exhibited protective effects against Hg(II)-mediated toxicity, which may be related to both antioxidant and Hg(II)-chelating activities.